THE STUDY OF BRAND RELATIONSHIP QUALITY AND CUSTOMER BEHAVIORAL INTENTIONS IN RELATION TO COSMETIC PRODUCTS MARKET - Dejkam, Seyedehfatemeh; Shafighi, Najla; Khavari, Seyed Abdollh (IJRDO - Journal of Business Management, 2018)
In today's business world, even the best service providers may make some mistakes. Since most services are labor-dependent and these services are simultaneously produced and consumed, service failures are fairly common in service providing sector. This is why brands are very important for service providing sectors. Due to the intangibility of services, makes it rather hard for customers to evaluate the quality and content of the services. Therefore, the service providing brands have the chance for reducing the risks of buying services. In marketing, it’s been proven that customers build a relationship with a brand and try to maintain it. This basically means that a brand can be a potential partner of this relationship. A great number of researchers in service providing market have stated that the quality of consumer-company relationship affects customer's reactions to service failures. Some of them believe this relationship can decrease customer's dissatisfaction after service failure. This study presents a definition of Fournier's brand relationship quality and examines its effect on customer's behavioral intentions, including word of mouth and repurchase, after service failure. In addition, a review of previous studies is presented. This is done using the theoretical models, which is extracted from research of Xie and Heung in 2012, and seven hypotheses are examined. The method used for data analysis is structural equation modeling and overall of 60 participants in “Management research and development center” have been included in this study. As well as examining the reliability of questionnaire by the experts, the stability of our questionnaire was tested using Cronbach's alpha test. After all six hypotheses were accepted. Findings of this study show that BRQ has a significant effect - both direct and indirect - on behavioral intentions. Thus, BRQ could play a key role in reducing the customer negative emotional responses. Therefore, if the institute tries to build a better relationship with its customers, in cases of service failure they can manage the negative effects in a more plausible way.